Contribution of MoS2 additives to the Microstructure and Properties of PM Copper Based Brake Material - Uzunsoy, Deniz; Kelesoglu, Erguen; Erarslan, Yaman (CARL HANSER VERLAG, 2009)
The effect of a MoS2 additive on the microstructural evolution and properties of copper based brake linings has been investigated in this study. It was found that the quantity of additive as well as sintering cycle has significant effect on the density and hardness values of the produced material. The microstructure of designed brake lining materials showed that copper based matrix was surrounded by MoS2 particles. The microstructural investigation also proved that the lower boiling point elements such as Pb in the as-supplied powder vaporise during sintering from the structure, and this result in an increase in the porosity amount by lowering the overall density of brake linings. The Vickers hardness of brake linings decreased with the addition of molybdenum disulphide particles. MoS2 addition reduces wear rate of samples due to the solid lubrication effect.
Keywords: FRICTION PERFORMANCE; INGREDIENTS; AL2O3; Materials Science